Incidence of scabies among patients treated at the Orbílio Machado Family Health Center, Bom Jesus do Itabapoana, Rio de Janeiro, Brazil - Ávila, Milena de Souza Furtado; Ávila, Marcos Loureiro Meireles; Manhães, Fernanda Castro; Mangiavacchi, Bianca Magnelli; Faial, Lígia Cordeiro Matos; Norberg, Paulo Roberto Blanco Moreira; Norberg, Antonio Neres; Filho, Renato Mataveli Ferreira; Ramos, Fabiana Pereira Costa; Ribeiro, Paulo Cesar (Seven Editora, 2023)
Scabies is a parasitic disease caused by the mite Sarcoptes scabiei and is an important public health problem. A retrospective study was conducted on the incidence of scabies among patients treated at the dermatology department of the Orbílio Machado Family Health Center, in the city of Bom Jesus do Itabapoana, state of Rio de Janeiro, Brazil. Among the 211 patients examined, 13 (6.16%) were diagnosed with scabies and 30.77% were five-year-olds. Although the incidence of scabies is low among the patients treated, it is suggested that actions to control scabies should focus on the child population at the beginning of school age. DOI:https://doi.org/10.56238/interdiinovationscrese-030